Step-by-step explanation:
<u>5</u><u>)</u><u> </u>2.4×10^-5 / 4.5×10^-11
- 2.4×10^-5= 0.000024
- 4.5×10^-11= 0.000000000045
=0.000024/0.000000000045
=24/1 × 1,000,000/45
=24,000,000/45
=533,333.33°
=5.33333°×10^5
**NOT SURE ABOUT THIS QUESTION
<u>6</u><u>)</u><u> </u>(4,-2)
<u>7</u><u>)</u> --------
<u>8</u><u>)</u>
- 2x + 3 = 5x - 2
- 2x - 5x = - 2 - 3
- -3x = -5
- x = -5/-3
- x = 1.66°
- 6x + 4 = 6x + 4
- 2 (2x + 3) = 8x - 2
- 4x + 6 = 8x - 2
- 4x - 8x = -2 - 6
- -4x = -8
- x = -8/-4
- x = 2
- -3x + 2 = -3x + 5
Letter be has no solution because it is broken down as "0x = 0"
Answer:
122/3 or 40.666667
Step-by-step explanation:
By applying algebraic handling on the two equations, we find the following three <em>solution</em> pairs: x₁ ≈ 5.693 ,y₁ ≈ 10.693; x₂ ≈ 1.430, y₂ ≈ 6.430; x₃ ≈ - 0.737, y₃ ≈ 4.263.
<h3>How to solve a system of equations</h3>
In this question we have a system formed by a <em>linear</em> equation and a <em>non-linear</em> equation, both with no <em>trascendent</em> elements and whose solution can be found easily by algebraic handling:
x - y = 5 (1)
x² · y = 5 · x + 6 (2)
By (1):
y = x + 5
By substituting on (2):
x² · (x + 5) = 5 · x + 6
x³ + 5 · x² - 5 · x - 6 = 0
(x + 5.693) · (x - 1.430) · (x + 0.737) = 0
There are three solutions: x₁ ≈ 5.693, x₂ ≈ 1.430, x₃ ≈ - 0.737
And the y-values are found by evaluating on (1):
y = x + 5
x₁ ≈ 5.693
y₁ ≈ 10.693
x₂ ≈ 1.430
y₂ ≈ 6.430
x₃ ≈ - 0.737
y₃ ≈ 4.263
By applying algebraic handling on the two equations, we find the following three <em>solution</em> pairs: x₁ ≈ 5.693 ,y₁ ≈ 10.693; x₂ ≈ 1.430, y₂ ≈ 6.430; x₃ ≈ - 0.737, y₃ ≈ 4.263.
To learn more on nonlinear equations: brainly.com/question/20242917
#SPJ1
Answer:
(-3,5)
Step-by-step explanation:
In reflections the x axis is the opposite only